Analysis of Mechanical Properties and Damage Behavior of Coal and Sandstone under Different Impact Velocities - Guoning Zhang; Yongjiang Yu; Wei Zhang (Shock and Vibration)
The fracture behavior and damage characteristics of coal and rock under dynamic failure are important factors in evaluating their mechanical characteristics. In this study, a split Hopkinson pressure bar (SHPB) was used to carry out dynamic tests on coal and sandstone samples, and the mechanical characteristics and energy evolution of coal and sandstone under different impact velocities were studied. The results show that with an increase in impact velocity, the dynamic compressive strength of coal and sandstone increases in a power function. The dynamic deformation modulus shows different evolution characteristics at different stages, and the average deformation modulus can better reflect the deformation characteristics of coal and sandstone in the loading stage. With the increase in strain rate, the incident energy (WI), reflected energy (WR), and transmitted energy (WT) increase in a quadratic function. The reflected and transmitted energy increases linearly with the increase in incident energy; the reflected energy growth rate of coal samples is higher than that of sandstone; and the transmitted energy growth rate of sandstone is higher than that of coal. The damage variable (Dd) of coal and sandstone shows an S-shaped trend with loading time. The peak damage degree of sandstone is more sensitive to the strain rate. The relevant results can provide a theoretical basis for coal mine disaster warning and tunnel support.